The Gender Gap in High School Physics: Considering the Context of Local Communities1. (1st April 2013) - Riegle‐Crumb, Catherine; Moore, Chelsea
<x xml:space="preserve">Abstract</x> Objectives We focus on variation in gender inequality in physics course‐taking, questioning the notion of a ubiquitous male advantage. We consider how inequality in high school physics is related to the context of students' local communities, specifically the representation of women in science, technology, engineering, and mathematics (STEM) occupations in the labor force. Methods This study uses nationally representative data from the National Longitudinal Study of Adolescent Health and its education component, the Adolescent Health and Academic Achievement Transcript Study. Results Approximately half of schools are characterized by either gender equality or even a small female advantage in enrollment in this traditionally male subject. Furthermore, variation in the gender gap in physics is related to the percent of women who are employed in STEM occupations within the community. Conclusion Our study suggests that communities differ in the extent to which traditionally gendered status expectations shape beliefs and behaviors.